Biosorptional studies on heavy metals in an up-flow packed bed reactor using biomaterials. (1st January 2013) - Begum, S. Sabarunisha; Muthukumar, S.; Yacin, S. Mohamed
Biosorption of copper, chromium, lead and cadmium in an up-flow packed-bed bioreactor with biosorbents [sanitary sewage sludge (SS), powdered coconut shell (PCS)] was conducted in a search for solutions to the environmental problem caused by heavy metals. Analysis of the results, demonstrated that the adsorbent had an extraordinary capacity for biosorption of the heavy metals, with a removal percentage of over 90% almost for all metals. The mechanism of the process was evaluated by FT-IR analysis and the functional groups employed in the process were determined. The presence of RNO2 peak at 1, 421 cm –1 for unloaded sanitary SS and the presence of C-H group of aromatic ring for unloaded PCS play a major role in adsorption process. In regeneration experiments, increase in sorption performance was observed during cycles of sorption-desorption indicates a maximum adsorption during the onset of the process. Kinetic models (Adams-Bohart model, Yoon and Nelson equation and Thomas model) analysed for the continuous packed-bed biosorption systems are used to determine the biosorption capacity, breakthrough curve of biosorbent and to design of treatment processes.